Professional competency instrument validity of assessment on teacher work performance - SUKADARI, SUKADARI (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The purpose of this research is to examine professional competency instrument validity on the assessment of teacher work performance based on the analysis of Aiken’s V and confirmatory factor analysis (CFA). The conclusions in this research, namely: 1) the results of testing the validity of Aiken’s V content of 0.75 in the professional competence instrument, this indicates that the instrument can be used because it has been fulfilled substantially, construction, and language aspects; 2) the validity test result by confirmatory factor analysis shows that the 16 items on professional competency can be used to assess teacher work performance. RESUMEN El propósito de este estudio es examinar la validez del instrumento de competencia profesional en la evaluación del desempeño docente basada en la V de Aiken y el análisis factorial confirmatorio (CFA). Las conclusiones de este estudio, a saber: 1) los resultados de la prueba de validez de contenido V de Aiken de 0,75 en la competencia profesional del instrumento, indican que el instrumento puede usarse porque ha cumplido sustancialmente los aspectos de construcción y lenguaje; 2) El resultado de la prueba de validez mediante el análisis factorial confirmatorio muestra que los 16 ítems sobre competencia profesional pueden usarse para evaluar el desempeño del maestro.